The relationship between talent management, job satisfaction and performance management in selected public higher learning institutions - Lukman@Zawawi, Mohamad; Kamal, M.Y. (2017)
Talent Management (TM) is originally practiced in the corporate sector for quite some time. Due to its practiced has successful in the corporate organization, Higher Learning Institution (HLI) around the world try to implement TM in their system. Practically, TM seems work in the education system. Up to that, Ministry of Higher Education (MOHE) has adopted and adapted TM in HLI. On the other hand, by practicing TM in any sectors, it will help to improve Job Satisfaction (JS) and Performance Management (PM) in the organization. Therefore, in this research, it will examine the relationship between TM towards JS and PM in selected public HLIs in Malaysia. Quantitative approach has been utilized as a part of a request to gather essential information from 238 respondents in selected public HLIs. Data gotten from this technique has been dissected utilizing IBM Statistical Package Social Sciences (SPSS). Accordingly, there was a direct relationship recorded between TM, JS, and PM. Notwithstanding, University A scored marginally higher relationship between's TM, JS and PM when contrasted with other two public HLIs. As a conclusion, every open HLI has their own particular mission and vision that should be accomplished. Along these lines, distinctive techniques may be utilized as a part of TM keeping in mind the end goal to get a decent association with JS and PM. In view of the discoveries got, it demonstrates that public HLI has taken their own particular activity to support their representative JS and PM by utilizing TM has one of the methodologies yet by one means or another, the systems took still should be observed and re-organized to get the great connection between these two factors.